PROGNOSTIC SIGNIFICANCE OF NON-SPECIFIC SYSTEMIC INFLAMMATION MARKERS IN PATIENTS WITH CORONARY HEART DISEASE - Romanova, V.O.; Kuzminova, N.V.; Ivankova, A.V.; Lozinsky, S.E.; Kniazkova, I.I.; Poberezhets, O.L.; Repetenko, M.V. (World of Medicine and Biology, 2024)
To evaluate the prognostic significance of markers of nonspecific systemic inflammation as predictors of unfavorable prognosis in patients with coronary heart disease, data from 135 patients with uncomplicated disease and 27 with unfavorable outcomes were analyzed. A 2-year prospective study showed that unfavorable cardiovascular events were significantly more common in patients with coronary heart disease and elevated levels of biomarkers of nonspecific systemic inflammation compared with those with lower values. The presence of myocardial infarction at baseline, a decrease in left ventricular ejection fraction
Keywords: coronary heart disease; patient prognosis; nonspecific systemic inflammation; high-sensitivity C-reactive protein; tumor necrosis factor-α; fibrinogen; blood lipids; atherosclerosis